Indirect Speech Act in Judy Christenberry's Novel the Cowboy's Secret Son: A Pragmatic Analysis - Muntiningsih, Ratna (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2013)
This paper presents the core of a descriptive theory of Indirect Speech acts, i.e. utterances used by the speaker to the hearer based on the three types of felicity conditions such as content condition, preparatory condition, and sincerity condition. The data examples takes from the English novel "The Cowboy's Secret Son" contains some of indirect speech act utterances that are included to the pragmatic study. The researcher explains and analyzes every utterance based on the theory of Yule (1996), Searle (1976, 1975), Austin (1962), Mey (1993), Bach and Harmish (1979), and Levinson (1983). The result of the research is founded that the speaker uses indirect speech act is to convey the request to the hearer to do something in the future. Moreover they use indirect speech act which has two meanings such as literal meaning and non-literal meaning or indirect meaning. In other words, they use indirect speech act to avoid the hearer to get upset, feel bad, angry and for politeness. And, generally they use indirect speech act because they have recognized the matters they are uttering.